Pendekatan Hak Asasi Manusia Islam Dalam Kerangka Ketatanegaraan (Analisis Pemikiran Rasyid Ridha tentang Negara dan Hak Individu) - Beldi Novriansyah; Muannif Ridwan; Bambang Sasmita Adi Putra (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2026)
This study aims to analyze the Islamic Human Rights approach within the framework of constitutional governance through an examination of Rashid Rida's thought on the state and individual rights. The research employs a normative legal research method with conceptual and historical approaches, focusing on the analysis of Rashid Rida's works and relevant literature on Islamic human rights and modern constitutionalism. The findings reveal that Rashid Rida viewed the state as an institution responsible for upholding Islamic law (Sharia), justice, and public welfare through the mechanism of shura (consultation) as the foundation of political participation. In his view, individual rights encompass freedom of religion, equality before the law, the right to justice, and the right to participate in government. However, the exercise of these rights is subject to the principles of social responsibility and the public interest (maslahah). The study also finds that Rashid Rida's concept of shura is relevant to the principles of modern constitutional democracy, particularly in terms of participation, accountability, and limitations on governmental power. Therefore, Rashid Rida's thought makes a significant contribution to the development of an Islamic human rights framework that is compatible with the modern rule of law and supports efforts to integrate Islamic values with universal human rights principles.